2015
DOI: 10.1111/adb.12336
|View full text |Cite
|
Sign up to set email alerts
|

Extended nicotine self‐administration increases sensitivity to nicotine, motivation to seek nicotine and the reinforcing properties of nicotine‐paired cues.

Abstract: An array of pharmacological and environmental factors influence the development and maintenance of tobacco addiction. The nature of these influences likely changes across the course of an extended smoking history, during which time drug seeking can become involuntary and uncontrolled. The present study used an animal model to examine the factors that drive nicotine-seeking behavior after either brief (10 days) or extended (40 days) self-administration training. In Experiment 1, extended training increased rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
2
13
1
Order By: Relevance
“…Our study also complements previous findings in clarifying the reinforcing-enhancing effects of Varenicline on a visual cue: namely, that these effects are only observed when individuals have been previously exposed to nAChR agonists. Contrary to our study, Clemens et al (2017) and Barrett et al (2018) showed that acute Varenicline increased the self-administration of a visual cue alone in the absence of nicotine. Furthermore, Levin et al (2012) briefly reports in drug-naïve animals, the reinforcing-enhancing effects of Varenicline on visual cues.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study also complements previous findings in clarifying the reinforcing-enhancing effects of Varenicline on a visual cue: namely, that these effects are only observed when individuals have been previously exposed to nAChR agonists. Contrary to our study, Clemens et al (2017) and Barrett et al (2018) showed that acute Varenicline increased the self-administration of a visual cue alone in the absence of nicotine. Furthermore, Levin et al (2012) briefly reports in drug-naïve animals, the reinforcing-enhancing effects of Varenicline on visual cues.…”
Section: Discussioncontrasting
confidence: 99%
“…However, and differently to our case, in these studies, rats had been previously exposed to either nicotine or Varenicline. In Clemens et al (2017), rats had been previously trained for nicotine + cue self-administration and Varenicline tested after seven self-administration of the cue alone, through a nicotine extinction-like procedure. In Barrett et al (2018), Varenicline was tested following a history of repeated passive exposure to nicotine administered after the cue self-administration sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Rats exhibited reliable and dose-dependent lever-press responses for nicotine self-administration. An inverted U-shaped dose-response curve was observed, which is consistent with other rat studies (Clemens et al 2015; Donny et al 1995; Hopkins et al 2012; Watkins et al 1999). Importantly, the present study further demonstrated that intraperitoneal pretreatment with menthol shifted the nicotine dose-response curve to the left.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, as in the present study, the rate of free‐access nicotine self‐administration varied considerably within a session (and see Clemens et al . ()), with the combination of frequency and dose bringing the estimated level of blood nicotine to an asymptote, and then maintaining it around that asymptote. These distinct within‐session self‐administration patterns might imply differences in the degree to which nicotine and cocaine seeking are controlled by the negatively and positively reinforcing effects of each drug when each is freely available.…”
Section: Discussionmentioning
confidence: 99%
“…These doses were selected to include (30 μg/kg/infusion) and bracket (15 and 60 μg/kg/infusion) that which typically produces the highest rate of responding on a nicotine dose–response curve (Clemens et al . ).…”
Section: Methodsmentioning
confidence: 97%